A Mechanistic Overview of Triptolide and Celastrol, Natural Products from Tripterygium wilfordii Hook F - Chen, Shao-Ru; Dai, Yan; Zhao, Jing; Lin, Ligen; Wang, Yitao; Wang, Ying (Frontiers in Pharmacology, 2018)
Triptolide and celastrol are predominantly active natural products isolated from the medicinal plant Tripterygium wilfordii Hook F. These compounds exhibit similar pharmacological activities, including anti-cancer, anti-inflammation, anti-obesity, and anti-diabetic activities. Triptolide and celastrol also provide neuroprotection and prevent cardiovascular and metabolic diseases. However, toxicity restricts the further development of triptolide and celastrol. In this review, we comprehensively review therapeutic targets and mechanisms of action, and translational study of triptolide and celastrol. We systemically discuss the structure-activity relationship of triptolide, celastrol, and their derivatives. Furthermore, we propose the use of structural derivatives, targeted therapy, and combination treatment as possible solutions to reduce toxicity and increase therapeutic window of these potent natural products from T. wilfordii Hook F.